The Use of the Spinner Educational Game to Improve English Learning Outcomes Among at Tonasa 2 Primary School - Muhammad Syaiful; Jumadi M Parenreng; Shabrina Syntha Dewi (Journal of Smart Education and Emerging Technology, 2026)
Background/Context: English is an important subject that needs to be taught effectively at the elementary school level. However, the learning process at SDS Tonasa 2 Pangkep was still dominated by lecture methods, resulting in low student interest and learning outcomes in English subjects. Objective/Purpose: This study aimed to improve the English learning outcomes of fourth-grade students at SDS Tonasa 2 Pangkep through the implementation of Game Spinner as a learning media. Method: This study used Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The research was conducted in two cycles involving 24 fourth-grade students. Data were collected through observation, tests, and documentation, then analyzed descriptively. Results: The results showed that the implementation of Game Spinner improved students’ English learning outcomes. In the pretest stage, only 9 students (37%) achieved the minimum mastery criteria. After the implementation of Game Spinner in Cycle I, the number of students who achieved mastery increased to 16 students (67%). In Cycle II, all students achieved mastery learning with a percentage of 100%. The average score also increased from 70 in the pretest to 77 in Cycle I and 84 in Cycle II. In addition, students became more active and motivated during the learning process. Conclusion: The use of Game Spinner as a learning media was effective in improving students’ English learning outcomes, motivation, and classroom participation among fourth-grade students at SDS Tonasa 2 Pangkep.